Developmenty of aqueous two-phase system (ATPS) to separate crude bioactive phenolics from Phanerochaete Chrysosporium biomass - Tan, Vin Chzee (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Natural antioxidants demand has increased globally due to the advantages and effect in various aspects, especially in pharmaceutical industry. Fungus Phanerochaete chrysosporium presents crude bioactive phenolics which act as antioxidant. The aim of this study was to develop an Aqueous Two Phase System (ATPS) to separate the phenolic compounds with high scavenging activity from Phanerochaete chrysosporium biomass. The main objective was to study the effect of salt concentration and pH on the partition of bioactive phenolics in solid-liquid ATPS. The second objective was to evaluate and compare the scavenging activity of phenolic extracted by ATPS with ascorbic acid. In order to extract the crude bioactive phenolics from the biomass of the fungus, a low cost and effective yet harmless to the environment ATP extraction technique was developed. The ATPS was developed by construct a phase diagram using appropriate concentration of the two phase forming components which in this case 80 % (w/w) of ethanol and 40 % (w/w) of K2HPO4. From the biphasic region indicated in the phase diagram, several points which give different composition of the components were selected to be test on the partition coefficient and recovery. The analytical result of total phenolic contents using Gallic acid as the standard was expressed in K and Rv. The best K (8.19) and Rv (97.81 %) was achieved by top phase of ATPS consisted of 50 % (w/v) ethanol and 20 % (w/v) K2HPO4 with 30 % (v/v) distilled water and 28 mg of biomass at pH 9.59. The capability of the phenolics in scavenging activity was tested by DPPH and the result was 81.77 % which considered high compared to the synthetic Ascorbic acid.